Young Black American’s Use of Afrocentric and Black Liberation Spiritual-Based Practices to Thrive Amid Racism: A Meta-Synthesis - Parker, Janise S. (Journal of cross-cultural psychology, 2025)
Researchers have proposed Afrocentrism and Black Liberation Theology as two culture-specific frameworks that may explain why spirituality contributes to Black American’s capacity to thrive, despite ongoing encounters with racism that can lead to diminished mental health. Still, scholars have not examined the connection between spirituality, racism, and mental health among young Black Americans (adolescents and emerging adults) through an integrative lens of Afrocentrism and Black Liberation Theology. A meta-synthesis permits researchers to synthesize and draw new meaning to existing qualitative studies. As such, we synthesized qualitative data from 16 studies that included the voices of approximately 288 Black adolescents and emerging adults to understand processes involved in their use of Afrocentric and Black Liberation spiritual-based practices to thrive and navigate mental health-related challenges sparked by racism and other intersecting forms of social oppression. Findings revealed four interconnected components: (a) Commitment to a Spiritual Identity, (b) Critical Consciousness, (c) Connecting to the Transcendent, and (d) Collectivism and Communal Support. This study shows how a meta-synthesis was employed to provide an in-depth understanding of Black youths’ use of spiritual resources to thrive amid racism and intersectional oppression.